Family Practitioner Services General Medical Statistics Northern Ireland : Administrative Data Quality Assessment Report.: Administrative Data Quality Assessment Report. (2021) - Northern Ireland., Business Services Organisation,; Northern Ireland Statistics & Research Agency,
No abstract available